Research productivity in the genetics of papillary thyroid carcinoma (1991-2020): a bibliometric analysis - Al Hamad , Mohammad; Lasrado, Savita; Albarbari , Hassan S.; Waris, Abu; Siddique , Nadeem; Khan , Muhammad Ajmal; Alharbi , Nouf; Mohiuddin, Shamim Shaikh; Parmar , Rupesh; Zeidan , Nehal A.; Al-Qassab , Aqilah T.; Menezes, Ritesh G. (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Papillary thyroid carcinoma accounts for 85% of thyroid follicular epithelial-derived cancers. The identification of pathogenetic mechanisms improved the understating of papillary thyroid carcinoma pathogenesis. The current study aims to examine the research productivity and trends in the genetics of papillary thyroid carcinoma from 1991 to 2020. Methods: The Web of Science Core Collection database was searched to retrieve the relevant literature. A search string was applied and 1,741 relevant records were selected for the analysis. Bibliometric techniques were used in the statistical analysis with the help of Biblioshiny (RStudio). Results: The growth in the number of publications was observed to be over a hundred publications per year since 2015. ‘Thyroid’ published the highest number of publications, followed by ‘Journal of Clinical Endocrinology & Metabolism’. ‘Nikiforov YE’ was identified as the most productive researcher with a total of 49 publications. Out of the top 20 most contributing researchers, seven belonged to Italy, and four were from the USA. ‘University of Pittsburgh’ contributed the highest number of publications. The top contributing countries in this field were the USA, China, and Italy. BRAF and RAS were among the frequently used keywords. Conclusions: This bibliometric review demonstrates that investigating the genetics underlying papillary thyroid carcinoma is a rapidly growing area of research. During the last two decades, China has been a significant contributor to the field. Besides, institutions in USA and Italy have significantly contributed to research in the genetics of papillary thyroid carcinoma. (www.actabiomedica.it)